Evolution of mindsight and psychological commitment among strategically interacting agents - Dimitry Rtischev (Games, 2016)
We study the evolution of strategic psychological capabilities in a population of interacting agents. Specifically,we consider agentswhich are either blind orwithmindsight, and either transparent or opaque. An agent with mindsight can observe the psychological makeup of a transparent agent, i.e., its logic, emotions, commitments and other elements that determine how it chooses actions. A blind agent cannot observe and opaque agents cannot be observed. Our assumption that mindsight and transparency are costly and optional exposes a middle ground between standard game theory without mindsight and evolution of preferences theory with obligatory and costless mindsight. We show that the only evolutionarily stable monomorphic population is one in which all agents are blind, opaque, and act-rational. We find that mindsight, transparency, and rule-rational commitments may evolve, albeit only in a portion of the population that fluctuates in size over generations. We reexamine the Ultimatum and Trust games in light of our findings and demonstrate that an evolved population of agents can differ significantly from a population of simplistic payoff-maximizers in terms of psychological traits and economic outcomes.
Keywords: C73; D83; D87; 330; theory of mind; mindsight; evolution of preferences; psychological commitment; act-rationality; rule-rationality; ultimatum game; trust game